New Mexico trivia - Ellis, Robert; Clark, Mary, 1963-; Clark, Jim, 1960- (Nashville, TN : Rutledge Hill Press, 1996)
New Mexico trivia is the who, what, when, where, and how book of the great state of New Mexico. Filled with interesting questions and answers about well-known and not-so-well-known facts of this colorful, historic state, New Mexico Trivia will provide hours of entertainment and education.
74134
Keywords: New Mexico -- Miscellanea